Given that cot theta = -2, we can rewrite this as:
cot theta = adjacent side / opposite side = -2
Let's assume adjacent side = -2x and opposite side = x. This assumption is made because the terminal side of theta lies in quadrant II, where x and -2x are both negative.
From the Pythagorean theorem, we have:
(-2x)^2 + x^2 = r^2
4x^2 + x^2 = r^2
5x^2 = r^2
r = x√5
Now, we can find the value of csc theta:
csc theta = hypotenuse / opposite side
csc theta = r / x
csc theta = x√5 / x
csc theta = √5
Therefore, csc theta = √5.
Find the exact value of csc theta if cot theta = -2 and the terminal side of theta lies in quadrant II.
1 answer